Sociodemographic Correlates of Clinical Laboratory Test Expenditures in a Major Canadian City. Issue 1 (12th June 2017) - Barber, Jocelyn; Guo, Maggie; Nguyen, Leonard T.; Thomas, Roger; Turin, Tanvir Chowdhury; Vaska, Marcus; Naugler, Christopher
Abstract: Objectives: The increasing cost of clinical laboratory testing is a challenge in our health care system. This study aims to calculate the annual clinical laboratory test costs attributed to patients in a major Canadian city and to correlate them to their sociodemographic variables. Methods: Retrospective cohort study involving patients who received clinical chemistry, hematology, and microbiology tests in 2011 in Calgary, Canada (n = 610, 409). Test volumes were obtained from a laboratory informatics database. Total expenditures per patient were calculated using estimated test costs and then combined with the 2011 Canadian Census Household Survey results to infer sociodemographic correlates. Results: While more women received laboratory testing (58.4%), men had slightly higher testing costs per capita. Except for Chinese, visible minority and Aboriginal populations had higher testing costs. There was an inverse correlation between testing cost and household income, and accordingly, higher costs were found in those without postsecondary education and the unemployed. Furthermore, hotspot mapping revealed the geographical distribution of patient test costs within the city. Conclusions: There is variation in testing costs for patients among different sociodemographic variables.